Microseisms at Madras associated with disturbances In the Bay of Bengal (MAUSAM, 1961)
Microseisms recorded at Madras associated with nearly all depressions and storms in the Bay of Bengal during the five-year period 1955 to 1959 have been examined.  Mean characteristics of microseisms in different months are described.  Case history of four microseismic storms are given. Regions in the Bay favourable for production of microseisms at Madras and otherwise are located and probable explanation for the existence of such regions offered.